2001
DOI: 10.1071/rd00039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glucose on the sex ratio of bovine IVM/IVF embryos cultured in vitro

Abstract: The effect of glucose in the medium used during in vitro culture on the sex ratio of bovine blastocysts derived from in-vitro-matured and in-vitro-fertilized oocytes was evaluated. Oocytes were matured and inseminated with mixed sperm from three bulls and were cultured in vitro in modified synthetic oviducal fluid medium with 10% fetal calf serum, with or without glucose supplementation. The overall rate of cleaved embryos that developed to expanded blastocyst in the medium without glucose (27.0%) was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 29 publications
7
68
0
3
Order By: Relevance
“…In our experiments, the phenomenon clearly results from a failure of female embryos cultured on the complex TCM-199 medium to make the transition to EB rather than from the faster growth of males. As suspected by Carvalho et al (22) and Gutierrez-Adan et al (47), glucose may be the reagent in the medium that is deleterious to female embryo development. Our data (Table 2) confirmed that a simple, glucose-free medium allowed female embryos to form EB as easily as males, and that the addition of 5.5 mM glucose to this medium was selectively detrimental to female EB formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our experiments, the phenomenon clearly results from a failure of female embryos cultured on the complex TCM-199 medium to make the transition to EB rather than from the faster growth of males. As suspected by Carvalho et al (22) and Gutierrez-Adan et al (47), glucose may be the reagent in the medium that is deleterious to female embryo development. Our data (Table 2) confirmed that a simple, glucose-free medium allowed female embryos to form EB as easily as males, and that the addition of 5.5 mM glucose to this medium was selectively detrimental to female EB formation.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the pentose phosphate pathway seems more active in in vitro-produced bovine blastocysts (48,51). In vitro culture also appears to lead to delayed X chromosome inactivation in female mammalian embryos (44,52) and to an increase in the mRNA for glucose 6-phosphate dehydrogenase and for other X-linked genes (47). Inactivation of the paternal X chromosome occurs in trophectoderm of female murine embryos at about the time of blastocele formation, whereas random X inactivation in the embryo proper occurs later (53,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, sex differences have also been reported in the placental protein human chorionic gonadotropin (hCG) [10]. Concentration of glucose and other nutrients during early cell division might also influence secondary sex ratio, as higher levels of glucose favour the development and the implantation of male blastocysts, providing a potential mechanism for sex-ratio variation in relation to maternal condition (in bovines [11] and in mice [12,13]). Over the past few years, there has been increasing evidence that females are also able to control the sex of their offspring at conception, thus overcoming the rigid process of chromosomal sex determination (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that more than one process could influence sex ratios (Sheldon & West 2004), and another mechanism by which sex ratios might be adjusted was suggested recently (Cameron 2004). Briefly, male and female conceptuses are sexually dimorphic in their response to glucose (Gutiérrez-Adán et al 2001) and in their ability to survive in mediums with different glucose concentrations ( Larson et al 2001). Added glucose enhances the development of the male conceptus, but inhibits female conceptus growth and development.…”
Section: Introductionmentioning
confidence: 99%